Single-chainpolymer nanoparticles via click crosslinking and effect of photoinduced radical combination on crosslink points - Keklik, Merve; Akar, Irem; Temel, Binnur Aydogan; Balta, Demet Karaca; Temel, Gokhan (WILEY, 2020)
Folding of azide functionalized polymer chains was obtained via the copper-catalyzed azide alkyne cycloaddition (CuAAC) methodology using a light-responsive crosslinker as the 'click' component. Subsequently, crosslinked junction points were combined with a photoinduced radical combination strategy to achieve more compact nanoparticles. The resultant folding particles possess smaller particle sizes and higher glass transition temperature values compared to their linear analogues. Fourier transform IR spectroscopy, SEC, DSC, dynamic light scattering,H-1 NMR and TEM techniques were used for characterization. (c) 2020 Society of Chemical Industry
Keywords: single-chain nanoparticles; click chemistry; folding chains; chain collapse; photoprocess; CHAIN NANOPARTICLES; POLYMERS; ROUTE; SIZE; Polymer Science